Promoting structural and species diversity in Great Lakes northern hardwoods: a conceptual model and its application. (25th August 2018) - Hupperts, Stefan F; Dickinson, Yvette L; Webster, Christopher R; Kern, Christel C
Abstract: Forest ecosystems are shaped by their historical disturbance regime. Structural and species diversity are driven by disturbance frequency, patch size and microsite disturbance severity in forests across the globe. Forest management in Lake State northern hardwoods, however, has primarily used high-frequency, low- to moderate-severity canopy disturbance and low-severity microsite disturbance harvesting techniques such as single-tree selection. Catastrophic disturbances during European settlement followed by the widespread and long-term use of uniform approaches to forest management have homogenized managed forests and created a need to emulate a fuller range of historically prevalent natural disturbances. We present a conceptual model based on complex adaptive forest management that proposes five primary factors including mean patch size, proportion disturbed, frequency, degree of exposed mineral soil and coarse woody debris input. This model demonstrates the need for a greater range of silvicultural systems to more closely emulate the range of variability associated with natural disturbance regimes. In Great Lakes northern hardwoods, using a greater variety of silvicultural systems including those with larger patch cuts and greater soil disturbance, may restore and promote structural and tree species diversity in these forests by creating greater microsite heterogeneity. Applying this conceptual model to forests more broadly, while still considering regionally specific factors, may help restore species and structural diversity and ultimately, ecosystem resilience.